Foreign direct investment from Vietnam to Laos in the context of integration - Thanh, Quang Phung; Nguyen, Nhat Linh (Bezpośrednie inwestycje zagraniczne z Wietnamu do Laosu w kontekście integracji, 2017)
Vietnam and Laos are the neighbour countries that have close relationships in politics, economic as well as in investment. Since early 2000s, Laos has swiftly become a targeted market in going global strategy of Vietnamese enterprises. Laos has been the biggest FDI recipient of Vietnam, comprised for around 25% of total outward FDI registered from Vietnamese firms. Vietnamese firms have played an increasingly important role in Lao economy, created nearly 40,000 jobs for local workers and contributed more than 70 million USD for social security in Laos (end of 2016). The article analyses some main features of FDI from Vietnam to Laos in the period 1994–2016, points out the “bottle necks” of the FDI flows such as the low level of spillover effect (with more than 60% of projects are vertical FDI); inappropriate investment structure (highly concentrate on mining industry, hydropower). The authors also suggest some policy implications for Vietnamese government and Laos government to boost the FDI inflows in the upcoming time
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 194-201
Keywords: outward FDI; Laos; Vietnam; wychodzące BIZ; Wietnam